Open-label, ascending dose, prospective cohort study evaluating the antiviral efficacy of Rosuvastatin therapy in serum and lipid fractions in patients with chronic hepatitis C - Patel, K. (2011)
HMG CoA reductase inhibition suppresses in vitro HCV replication through depletion of cellular sterol proteins such as geranylgeraniol. Our aims were to prospectively evaluate the changes in serum and lipid fraction HCV RNA with Rosuvastatin in non-responder (NR) patients with CHC. A total of 11 patients with CHC genotype-1 received Rosuvastatin at 20 mg qd (weeks 0–4), 40 mg qd (weeks 5–12), with 4 week follow up. Lipid fractions were separated by a sucrose density gradient ultracentrifugation, HCV RNA determined at wks 0, 2, 4, 8, 12, 16 in serum, and in selected very low- (VLDF) to high-density (HDF) lipid fractions. A reduction in LDL and total cholesterol (TC) was not accompanied by significant decline in HCV RNA. At baseline, there was an inverse correlation between HDL and HCV RNA (ρ = −0.45, P = 0.036). At 20 mg, there was correlation between change (Δ) in TG and Δ HCV RNA (ρ = 0.75, P = 0.007), Δ ALT and Δ TC (ρ = −0.64, P = 0.03) and Δ LDL (ρ = −0.67, P = 0.02). At 40 mg, Δ TG maintained a positive correlation with Δ HCV RNA (ρ = 0.65, P = 0.03). There was a group difference for HCV RNA in relation to lipid fractions (P = 0.04) but not study time intervals (P = 0.17); mean log HCV RNA was greater in VLDF compared to HDF (5.81 ± 0.59 vs 5.06 ± 0.67, P = 0.0002) with no other differences to study time intervals (P = 0.099). Short-term Rosuvastatin monotherapy is not associated with significant changes in serum or lipid fraction HCV RNA in NR patients. HCV co-localizes with the lowest density lipid fractions in serum.